Zakat Profesi dan Pemanfaatannya di Kota Ternate: Analisis Hukum Islam dan Undang-Undang Nomor 23 Tahun 2011 - Burhanuddin Onde; Basaria Nainggolan; Abu Sanmas (Program Studi Hukum Keluarga dan Hukum Ekonomi Syariah, Program Pascasarjana Institut Agama Islam Negeri (IAIN) Ternate, 2022)
This study aims to answer the problem of how professional zakat and its utilization in the city of Ternate and how the analysis of Islamic law and Law Number 23 of 2011 on professional zakat and its utilization in the city of Ternate. The method used is qualitative with an empirical juridical approach. The data analysis method used is qualitative data analysis using inductive and deductive thinking frameworks. Based on the results of the discussion, it can be concluded that the collection and management of zakat by the Amil Zakat Agency of the City of Ternate, especially professional zakat for ASN within the Ternate City Government is maximized because many muzakki (Civil State Civil Apparatuses of Ternate City) have complied with the Circular and Regional Regulations from the Government. The results of the collection of professional zakat are widely felt by the community, especially the eight groups who are entitled to receive it and those in need. In Islamic law, in essence, zakat issued from the results of one's profession (work) is an obligation, this is in line with the regulations made by the government through Law number 23 of 2011. In addition, the utilization in its distribution is in accordance with the provisions of Islamic law and the demands of the law, namely that it is given to eight groups and people who need it for their needs.